Met or matched expectations: what accounts for a successful back pain consultation in primary care?. (17th June 2011) - Georgy, Ehab E.; Carr, Eloise C.J.; Breen, Alan C.
Abstract Background Patients' as well as doctors' expectations might be key elements for improving the quality of health care; however, previous conceptual and theoretical frameworks related to expectations often overlook such complex and complementary relationship between patients' and doctors' expectations. The concept of 'matched patient–doctor expectations' is not properly investigated, and there is lack of literature exploring such aspect of the consultation. Aim The paper presents a preliminary conceptual model for the relationship between patients' and doctors' expectations with specific reference to back pain management in primary care. Methods The methods employed in this study are integrative literature review, examination of previous theoretical frameworks, identification of conceptual issues in existing literature, and synthesis and development of a preliminary pragmatic conceptual framework. Outcome A simple preliminary model explaining the formation of expectations in relation to specific antecedents and consequences was developed; the model incorporates several stages and filters (influencing factors, underlying reactions, judgement, formed reactions, outcome and significance) to explain the development and anticipated influence of expectations on the consultation outcome. Conclusion The newly developed model takes into account several important dynamics that might be key elements for more successful back pain consultation in primary care, mainly the importance of matching patients' and doctors' expectations as well as the importance of addressing unmet expectations.